2022
DOI: 10.1039/d1ob01919h
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis applied to carbohydrates: from roots to current developments

Abstract: Organocatalysis emerged in the last decades as a powerful tool to the synthesis complex molecules. In the field of carbohydrates, it found widespread utilization in the synthesis of rare and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Nowadays, they have been applied in several reactions, including Michael addition reaction, aldol reactions, or Morita-Baylis-Hillman reaction. [3,4] Among them, sugar-derived ketones have been employed for the synthesis of optically active epoxides. [5] In 1996, the seminal work by Shi reported that a fructose-derived chiral ketone is able to efficiently perform the asymmetric epoxidation of olefins after its in-situ conversion into a chiral dioxirane by treatment with Oxone or H 2 O 2 in basic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, they have been applied in several reactions, including Michael addition reaction, aldol reactions, or Morita-Baylis-Hillman reaction. [3,4] Among them, sugar-derived ketones have been employed for the synthesis of optically active epoxides. [5] In 1996, the seminal work by Shi reported that a fructose-derived chiral ketone is able to efficiently perform the asymmetric epoxidation of olefins after its in-situ conversion into a chiral dioxirane by treatment with Oxone or H 2 O 2 in basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalysis developed as an alternative route to produce chiral molecules, and carbohydrates also emerged as chiral scaffolds for catalyst design and synthesis. Nowadays, they have been applied in several reactions, including Michael addition reaction, aldol reactions, or Morita–Baylis–Hillman reaction [3,4] . Among them, sugar‐derived ketones have been employed for the synthesis of optically active epoxides [5] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The increasing demand for scaffolds in the development of new organocatalysts has spurred researchers to explore carbohydrates with distinctive characteristics, making them promising candidates for organocatalysis. 3,4 In the last years, several ketones based on sugar skeletons have been developed to be exploited in Shi-type epoxidation. In 1996, Shi et al reported the use of a fructosederived ketone as an organocatalyst for enantioselective epoxidation of trans-olens with potassium peroxymonosulfate (Oxone) as oxidant.…”
Section: Introductionmentioning
confidence: 99%